THE NOVEL GOES UTOPIA: ON VOLODYMYR VYNNYCHENKO’S THE SUN MACHINE - BEKHTA, Natalya (Studia Universitatis Babeș-Bolyai Philologia, 2025)
The Novel Goes Utopia. On Volodymyr Vynnychenko’s The Sun Machine. This article contributes to the project of “un-noveling” literary theory by drawing attention to the homogenizing tendency in (world-)literary theory, caused by its strong focus on the genre of the novel, however global and all-encompassing that genre may be understood. In order to discern the limits and limitations of the novel, it is examined in opposition to utopia. In particular, a discussion of Volodymyr Vynnychenko’s bestselling “utopian novel” The Sun Machine (1928) and its critical reception draws out a host of critical-theoretical presuppositions related to the novel and questions of aesthetics, politics and narrative. An “unnovelistic” genre of utopia also invites a brief discussion of the semiotic method of reading (for) utopia and the problem of binary oppositions for literary theory more generally. It is through these two angles that the article proposes to address the overarching theme of the special issue, post-novel, and one of its sub-interests – the interpretive methods grounded in semiotics. REZUMAT. Romanul spre calea utopiei. Despre Mașina Soarelui de Volodymyr Vynnychenko. Acest articol contribuie la proiectul deconstrucției genului romanesc în teoria literară prin descrierea tendinței de omogenizare din teoria (mondial-)literară, cauzată de focalizarea acesteia asupra genului romanesc, oricât de global și atotcuprinzător ar fi acesta înțeles. Pentru a discerne limitele și limitările romanului, acesta este examinat în opoziție cu utopia. În special, o discuție a „romanului utopic”, bestsellerul Mașina Soarelui (1928) de Volodymyr Vynnychenko și a receptării sale critice, scoate la iveală o serie de presupoziții critico-teoretice legate de roman și de chestiuni de estetică, politică și narațiune. Un gen non-romanesc al utopiei invită, de asemenea, la o scurtă discuție despre metoda semiotică de a citi (pentru) utopie, dar și despre problema opozițiilor binare în raport cu teoria literară în general. Prin aceste două perspective, articolul propune abordarea temei generale a numărului special, post-romanul, și a unuia dintre sub-interesele sale – metodele interpretative întemeiate pe semiotică. Cuvinte-cheie: roman, „roman global”, utopie, ficțiune ucraineană, teorie literară mondială. Article history: Received 15 June 2025; Revised 31 August 2025; Accepted 05 September 2025; Available online 24 September 2025; Available print 30 September 2025